Towards a fun and playful model for young children's foreign language learning - Lawrence, Daniel (2017)
This thesis proposes a model for young children's foreign language learning with a focus on fun and playfulness as well as emotional needs. The model is based on a wide range of literature on children's development, education, and foreign language learning specifically.